EVALUASI PELAKSANAAN PROGRAM MOBIL PUSAT LAYANAN INTERNET KECAMATAN (M-PLIK) DI KOTA PEKANBARU TAHUN 2012-2013 - Putra, Yogi Dwi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Internet Service Center Subdistrict (PLIK) and Mobile Internet Service Center Subdistrict (MPLIK) is a program of the Ministry of Communication and Information of the Republic of Indonesia (Kemkominfo RI), with the aim of supporting the expansion of Internet access services for the wider community and as the acceleration of the increase in affordability of equity of services and utilization for the purpose increase intelligence and social welfare, especially in the districts. Car internet service provider districts is the mandate of the Regulation of the Minister of Communication and Information No.19 / PER / M.KOMINFO / 12/2010. The problem in this research, MPLIK not operate properly according to Standard, lack of coordination and the seriousness of the manager / managing partner in the operation MPLIK and more often to settle because of limited operational funds, distribution MPLIK has not been done according to the target, coordination and dissemination program MPLIK with Local Government relatively minimal, Based on this background, authors are encouraged to do research with the title